Study of the effect of salt deposition on production capacity and storage capacity in underground gas storage - Zhongxin, Ren; Xiaoping, Yang; Dawei, Chang; Ning, Wang; Da, Meng (Frontiers in Earth Science, 2024)
Underground gas storage (UGS) is the most economical and effective means to guarantee stable gas supply. During gas production process, the evaporation of formation water leads to the increase of water content in the gas, and the salinity of the remaining formation water increases. This work applied numerical simulation to analyze the effect of salt deposition on flowing bottomhole pressure, production capacity and storage capacity. The simulation results show that the minimum and maximum pressure of UGS is more likely to be reached during multi-cycle production under the conditions of salt deposition. Under the initial water condition, reservoir drying can improve the gas storage capacity. At the end of the tenth cycle, the storage capacity increases by 1.4%. It is concluded that the study on the impact of formation water evaporation on storage capacity is helpful for the prevention and control of salt formation water in UGS with high salinity.